The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1177/1524838008320221
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Drugs and Alcohol in Drug-Facilitated Sexual Assault

Abstract: The rate of drug-facilitated sexual assault (DFSA; when an incapacitating drug is administered surreptitiously to facilitate sexual assault) is perceived to be increasing in the United Kingdom and elsewhere, causing international concern. This article examines evidence that quantifies the contribution of drugs in instances of alleged DFSA, identifies the substances involved, and discusses the implications of these findings. Of 389 studies examined, 11 were included in this review. The only study to consider co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 29 publications
0
40
0
6
Order By: Relevance
“…35,36 Unexpected (ie, no known history of drug exposure to the specific drug) positive toxicology results were found in 49% of the suspected DFSA cases; results showed cannabinoids (40%) and cocaine (32%) most frequently. Similar individual studies and systematic reviews 37 from the United States, Canada, United Kingdom, Australia, and other countries have reported that less than 2% of cases of DFSA are associated with common date rape drugs. 34 -36, 38 -43 There may be a greater index of suspicion for such use in geographic areas where flunitrazepam and similar drugs are legal or more accessible (eg, Mexico and near border areas).…”
Section: Use Of Substancesmentioning
confidence: 57%
“…35,36 Unexpected (ie, no known history of drug exposure to the specific drug) positive toxicology results were found in 49% of the suspected DFSA cases; results showed cannabinoids (40%) and cocaine (32%) most frequently. Similar individual studies and systematic reviews 37 from the United States, Canada, United Kingdom, Australia, and other countries have reported that less than 2% of cases of DFSA are associated with common date rape drugs. 34 -36, 38 -43 There may be a greater index of suspicion for such use in geographic areas where flunitrazepam and similar drugs are legal or more accessible (eg, Mexico and near border areas).…”
Section: Use Of Substancesmentioning
confidence: 57%
“…Son medicamentos -benzodiazepinas (flunitrazepan, lorazepan…) hipnóticos (zopiclona, zolpiden…), neurolépticos, sedantes o anestésicos-utilizados como DFAS y que normalmente son diluidos en la bebida alcohólica de la víctima que las acaba ingiriendo de forma involuntaria provocándole somnolencia, quedando la víctima en total estado de inconsciencia (Beynon et al, 2008;Jones et al, 2012).…”
Section: Benzodiazepinas E Hipnóticosunclassified
“…Los datos disponibles hasta la fecha sugieren que la SQ sigue siendo un fenómeno relativamente infrecuente y de características criminológicas propias (Beynon et al, 2008 No debemos olvidar que el 100% de los casos de violencia sexual con violencia y en al menos 2/3 partes de los demás casos, se evidencian reacciones emocionales considerables, especialmente miedo, depresión y rabia que llevan a estas mujeres a presentar cambios significativos en sus estilos de vida (Shapland, 1990).…”
Section: Conclusionesunclassified
“…Bu faktörler sonucu toplumda İKCS vakalarının yaygın olduğu kanısı uyanmaktadır. Ancak asıl tehlike İKCS olduğu iddia edilen vakalarda gönüllü ilaç tüketiminin çok büyük baskınlığının olduğunu göz ardı etmektir [57]. GABA merkezi sinir sisteminin (MSS) primer inhibitör nörotrans-mitter maddesidir.…”
Section: Cinsel Saldırıları Kolaylaştırabilen İlaçların Kullanım Yüzdunclassified